Charleston and Monk's House : the intimate house museums of Virginia Woolf and Vanessa Bell - Hancock, Nuala (Edinburgh University Press, 2012)
The interwoven biographies of Virginia Woolf and Vanessa Bell and the houses they lived in What can we learn from a commemorative house? What biographical narratives emerge as we travel through the spaces of another's home? This new study unveils the revelatory potential of the house museum to inform and enrich our understanding of the lived past of its former inhabitants. It focuses on the emotionally textured interiors of Charleston and Monk's House, the literary/artistic house museums of Virginia Woolf and Vanessa Bell, seeking out traces of their shared biography. Fresh perspectives unfold on Woolf's and Bell's' sisterhood and their continuous artistic exchange, as we shadow their daily lives through the richly painted rooms and atmospheric gardens of their former Sussex homes. Discover these celebrated artists in a different light - animated, moving, handling the tools of their related arts and brought vividly to life through the tangible fabric of their past living. Key Features:. * Reveals, through an emplaced investigation, the potential of Charleston and Monk's House to illuminate the shared histories of Virginia Woolf and Vanessa Bell * Provides new insights into aspects of Woolf's and Bell's lives * Explores the poetic relationship between house and dweller, and points the way to a richer interpretative response to house museums * Demonstrates the central role of embodied and sensory responses, alongside intellectual analysis, as tools in a multi-dimensional interpretation of the material world Keywords:. Virginia Woolf, Vanessa Bell, Charleston, Monk's House, House-Museum, Spatial Poetics, Biography, Writing, Painting, Phenomenology